2011
DOI: 10.4103/2231-4040.90883
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological properties of Mikania scandens (L.) Willd. (Asteraceae)

Abstract: Mikania scandens (L.) Willd. (Asteraceae), known as climbing hemp weed in English, is a herbaceous climbing vine grown as a weed throughout the plains of the Indian subcontinent. The present study evaluated some neuropharmacological properties of hydroalcoholic extract of aerial parts from M. scandens (HAMS) in experimental animal models. HAMS (at 250 and 500 mg/kg body weight, i.p.) was evaluated for central antinociceptive activity by tail flick method. Locomotor depressant activity was measured by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Furthermore, no significant effect in the locomotor activity was observed with crude E. milii methanolic extract however a significant decrease ( P < 0.01) was observed with Au-EM as compared to diazepam ( P < 0.001), thus indicating that its sedative properties is due to its motor depressant effect in mice. Most of the centrally acting analgesics influence the locomotor activities by reducing the motor activity because of their CNS depressant property [ 66 ]. Locomotor activity is considered as an index of wakefulness or alertness of mental activity and a decrease activity is indicative of calmness and sedation as a result of reduced CNS excitability [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no significant effect in the locomotor activity was observed with crude E. milii methanolic extract however a significant decrease ( P < 0.01) was observed with Au-EM as compared to diazepam ( P < 0.001), thus indicating that its sedative properties is due to its motor depressant effect in mice. Most of the centrally acting analgesics influence the locomotor activities by reducing the motor activity because of their CNS depressant property [ 66 ]. Locomotor activity is considered as an index of wakefulness or alertness of mental activity and a decrease activity is indicative of calmness and sedation as a result of reduced CNS excitability [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study provided evidence that the extracts reduced locomotor activity confirming its CNS depressant potential. Locomotor activity is considered as an index of alertness and a reduction of it is an indicative of sedative or CNS depressant activity [40]. Gamma-aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the central nervous system [41], which is also involved in other physiological functions related to behavior and in various psychological and neurological disorders such as epilepsy, anxiety, depression, parkinson syndrome, and alzheimer's disease [42].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigation of the phytoconstituents of medicinal plants suggests that many flavonoids and neuroactive steroids are ligands for GABA A receptors in the central nervous system which suggests that they can act as benzodiazepine-like agents [40]. It has also been reported that some flavanoids exhibit high affinity binding to the benzodiazepine site of GABA A receptors.…”
Section: And 5)mentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that flavonoids especially apigenin and EGCG have hypnotic effects. Flavonoids are ligands for GABAA receptors in the CNS that show effects such as benzodiazepines (Bhattacharya et al, 2011). These flavonoids exhibit high affinity bonds in the GABAAbenzodiazepine binding receptor Roth and Roehrs, 2003;Rustay et ak., 2003) so that they have anxiolytic effects, sedation, decreased motor activity (Netto et al, 2009), and hypnotics (Olayiwola et al, 2007).…”
Section: Male Mice In Vivo Test Effect Of Functional Beverages On Motmentioning
confidence: 99%